Predictors of job satisfaction among community development officers in Oyo state, Nigeria (2017)
Job satisfaction (JS) among community development (CD) officers in the various local government areas (LGAs) in Oyo State has been reported to be very low, thereby leading to absenteeism and high turnover rate. This study examined Predictors of Job Satisfaction (leadership, supervision, working conditions, work environment, career advancement opportunities, work placement, remuneration, training and development) among job satisfaction of CD officers in Oyo State, Nigeria. Descriptive survey design was adopted. Multi-stage sampling procedure was used. Five local government areas with high number of CD officers were purposively selected front each of the three senatorial districts in the state, while total enumeration technique was used to select respondents front the fifteen (15) LGAs. A total of 771 CD officers were sampled. The independent variables considered during this study were leadership, supervision, working conditions, work environment, career advancement opportunities, work placement, remuneration, training and development. Quantitative Data were analysed using descriptive statistics, multiple regression and Pearson product moment correlation at 0.05 level of significance. The results show job satisfaction is affected by leadership attitude (r=0.95), supervision (r=0.72), working conditions (r=0.77), work environment (r=0.64), career advancement opportunities (r=0.85), work placement (r=0.82), remuneration (r=0.64), training and development (r=0.77) and job satisfaction (r=0.85). Among the predictors of job satisfaction considered, working condition had the highest contribution to the prediction (job satisfaction) at P <0.05. The study revealed that a positive significant relationship exist between job satisfaction and working condition. It is recommended that there is the need for government, policy makers and community development practitioners to put into considerations predictors of job satisfaction